Association Between Patient Characteristics and Diet Profile with Kirsten rat sarcoma Kras and Neuroblastoma rat sarcoma (Nras) Gene Mutation in Colorectal Cancer - Dedy Indra Praja; Helena Helena; Bogi Pratomo (The Indonesian Society for Digestive Endoscopy, 2019)
Background: Colorectal cancer is the third most common cancer according to American Cancer Society. It is also the third most common cause of death in men and women in US. Colorectal cancer encompasses 5% of all cancer and 29% of gastrointestinal cancer with men and women ratio is about 3:1. More than 1/3 of colorectal cancer occur below the age of 45 years. Mutation in Kirsten rat sarcoma (KRAS) gene was found in 30-50% of colorectal cancer in which it was suggested to associated with increase proliferation and decrease apoptosis. This study aimed to analyze the association between diet profile and KRAS gene mutation.Method: This study was a cross sectional study. Data was collected from medical records of colorectal cancer patient in Dr. Saiful Anwar General Hospital, which included KRAS gene mutation analysis.Results: There were 12 subjetcs included in this study. Four subjects (33.3%) had gene mutation with 3 subjects (75%) had positive KRAS mutation and 1 subjects (25%) had positive Neuroblastoma rat sarcoma (NRAS) mutation. In non-mutation group, it had been found a higher frequency of green leaf vegetables diet, in comparison with mutation group (p = 0.023). There was positive correlation between green leaf vegetables diet with gene mutation.Conclusion: Mutation of KRAS and NRAS mutation in colorectal carcinoma were found in 33.3% of subjects. Data analysis showed positive association between low green leaf vegetables diet with KRAS and NRAS mutation.